THE EFFECT OF FAMILY PARENTING ON EARLY MARRIAGE KNOWLEDGE IN ADOLESCENTS IN SENIOR HIGH SCHOOL 1 PLUS COMPUTER NETWORK ENGINEERING IN 2021 - Zubairi, Ahmad; Seftiana, Nova (Journal of Vocational Nursing, 2021)
Introduction: Early marriage that occurs cannot be separated from parental support, they have the perception that marrying off their children at an early age to keep their children safe, and put pressure on children not to continue their education due to low economics. Methods: To find out how the relationship between parenting families with the perception of early marriage in adolescents, Knowing the description of parenting patterns for early marriage in adolescents. Research Methods: This study is a quantitative study, with a descriptive correlation type of design. Samples were taken through random sampling with a cross sectional approach. Results: From the results of bivariate analysis using the chi square test, the p-value of 0.038 (<0. 05) can be concluded so that it can be concluded that there is a relationship between family parenting patterns and perceptions of early marriage in adolescents in Senior High School 1 Plus Computer Nerwork Engineering in 2021. Conclusion: The results of the respondents were 50 female students and 30 male students. The results of the respondents' parenting in the family were 42.5% good, 57.5% good enough, and 0 bad parenting